Effect on Conductance, Viscosity and Ultrasonic Velocity Using Sodium Tetradecyl Sulphate as Surfactant with Butanol/Pentanol/Hexyl amine as Co-surfactant and Heptane/Hexane as Oil - Vashist, S.L.; Handa, S.P.; Puri, Vaneet; Sakhuja, Niti (Asian Journal of Chemistry, 2010)
In the present investigation, water in oil microemulsions have been prepared with sodium tetradecyl sulphate (STS) as surfactant and butanol/ pentanol/hexyl amine as co-surfactant, the continuous phase being hexane/heptane. Various physical measurements such as conductance, viscosity and ultrasonic velocity have been carried out in these microemulsions. With these co-surfactants there is a change in conductance as compared to pentanol. With the change of oil there is a notable difference in conductance behaviour in case of butanol but in case of pentanol with change of oil the conductance behaviour is similar; only the use of hexane causes conductance value to suppress. This is also the case if hexylamine is used as co-surfactant; only the constant value of conductance is lower as compared to hexane case. In case of hexane there are two maxima as compared to one in heptane; the viscosity behaviour is not much affected by change of oil; only sharp increase in viscosity is exhibited at a lower volume fraction in case of hexane as compared to heptane. The value of ultrasonic velocity shifts to a lower value when hexane is replaced with heptane when butanol is the cosurfactant. This is also the case when butanol is replaced by pentanol as co-surfactant. Surprisingly, when hexyl amine is used as co-surfactant its ultrasonic behaviour is very similar to the one shown by microemulsions containing butanol/pentanol as co-surfactant.